2018
DOI: 10.1088/1748-0221/13/04/c04004
|View full text |Cite
|
Sign up to set email alerts
|

Advances in indirect detector systems for ultra high-speed hard X-ray imaging with synchrotron light

Abstract: We report on indirect X-ray detector systems for various full-field, ultra high-speed X-ray imaging methodologies, such as X-ray phase-contrast radiography, diffraction topography, grating interferometry and speckle-based imaging performed at the hard X-ray imaging beamline ID19 of the European Synchrotron—ESRF. Our work highlights the versatility of indirect X-ray detectors to multiple goals such as single synchrotron pulse isolation, multiple-frame recording up to millions frames per second, high efficiency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Recently, we demonstrated that the application of a fringe scan can improve the spatial resolution and signal-tonoise ratio of the tomograms obtained in grating-based X-ray interferometry, and successfully realized quantitative X-ray phase tomography for a rotating sample with millisecondorder measurement time (Yashiro et al, 2018a). A higher temporal resolution can be realized with a higher sample rotation speed, if an X-ray source with higher-brilliance, such as an undulator or an X-ray free-electron laser, is used (Rack et al, 2014;Olbinado et al, 2017Olbinado et al, , 2018Escauriza et al, 2018;Vagovič et al, 2019). However, their beam sizes are of millimetre-order, limiting their FOVs, and the higher rotation speed further limits their application.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that the application of a fringe scan can improve the spatial resolution and signal-tonoise ratio of the tomograms obtained in grating-based X-ray interferometry, and successfully realized quantitative X-ray phase tomography for a rotating sample with millisecondorder measurement time (Yashiro et al, 2018a). A higher temporal resolution can be realized with a higher sample rotation speed, if an X-ray source with higher-brilliance, such as an undulator or an X-ray free-electron laser, is used (Rack et al, 2014;Olbinado et al, 2017Olbinado et al, , 2018Escauriza et al, 2018;Vagovič et al, 2019). However, their beam sizes are of millimetre-order, limiting their FOVs, and the higher rotation speed further limits their application.…”
Section: Discussionmentioning
confidence: 99%
“…Olbinado et al [64] extended their previous research by examining three methods of obtaining high and ultra-high-speed synchrotron X-ray imaging, shown in a simplified manner in Figure 4. The method the authors examine is using a frame transfer CMOS camera with in-pixel storage, to achieve frame rates above 1 million FPS without reducing the number of pixels in the image frame.…”
Section: Where Next?mentioning
confidence: 99%
“…This method is a more sensitive form of XPCI and is achieved by using X-ray optics that directly measure beam refraction in grating interferometry and tracking near-field speckles introduced by randomly structured material. This allowed the authors to obtain an effective pixel size of 1.625 µm with a time resolution of 70.4 µs [64]. This third method the authors describe is similar to DIC and hence could be adapted to provide high and ultra-high-speed 3D DIC, with very small spatial resolution.…”
Section: Where Next?mentioning
confidence: 99%
“…Such modalities are straightforward to be utilized for the retrieval of several contrast modalities from a single projection. Thus, it enables multimodal monitoring dynamic systems at different timescales: from real-time imaging [11] to fast imaging at the scale of microseconds [5,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%